Corticospinal Tract Impairment of Patients With Parkinson’s Disease: Triple Stimulation Technique Findings - Xu, Dan; Ding, Qingyun; Wang, Han (Frontiers in Aging Neuroscience, 2020)
Background: The corticospinal tract impairment is no longer an absolute exclusion in the updated Movement Disorder Society Parkinson’s disease criteria. Triple stimulation technique (TST) is an accurate method to quantitatively assess the integrity and impairment of corticospinal pathway in a variety of neurological diseases. This study aims to evaluate the corticospinal tract impairment in Parkinson’s disease (PD) patients using TST. Methods: Ten PD patients, 19 multiple system atrophy parkinsonian variant (MSA-P) patients and 12 healthy controls (HC) were sequentially recruited in this study. Information of age, disease duration, pyramidal signs and Hoehn-Yahr(H-Y) stage was obtained from all patients. The TST was assessed at right abductor digiti minimi for HCs and both sides for patients. Chi-square test was used for categorical variables and variance analysis was performed for continuous variables in comparing the difference among PD, MSA-P and HC, plus the post-hoc tests for pairwise comparisons. Results: All subjects were age and gender matched. There was no significant difference in disease duration (p=0.855), H-Y stage (p=0.067) and the percentage of pyramidal signs present (p=0.581) between MSA-P and PD patients. The mean TST ratio was 55.5±32.2%, 81.7±19.8% and 96.8±3.0% for PD, MSA-P and HCs, correspondingly. PD patients had significant lower TST amplitude ratio than MSA-P and HCs. The TST ratio of MSA-P was lower than HCs, but there was no significant difference (p=0.160). Additionally, it was significant higher in percentage of abnormal TST ratio between PD patients and MSA-P (p=0.010). Conclusions: The corticospinal tract impairment is not a rare manifestation in PD and can be quantitatively evaluated with TST. The result needs to be verified in amplified sample.